Brain size and neuron numbers drive differences in yawn duration across mammals and birds - Massen, Jorg J M; Hartlieb, Margarita; Martin, Jordan S; Leitgeb, Elisabeth B; Hockl, Jasmin; Kocourek, Martin; Olkowicz, Seweryn; Zhang, Yicheng; Osadnik, Christin; Verkleij, Jorrit W; Bugnyar, Thomas; Němec, Pavel; et al. (Communications biology, 2021)
Recent studies indicate that yawning evolved as a brain cooling mechanism. Given that larger brains have greater thermolytic needs and brain temperature is determined in part by heat production from neuronal activity, it was hypothesized that animals with larger brains and more neurons would yawn longer to produce comparable cooling effects. To test this, we performed the largest study on yawning ever conducted, analyzing 1291 yawns from 101 species (55 mammals; 46 birds). Phylogenetically controlled analyses revealed robust positive correlations between yawn duration and (1) brain mass, (2) total neuron number, and (3) cortical/pallial neuron number in both mammals and birds, which cannot be attributed solely to allometric scaling rules. These relationships were similar across clades, though mammals exhibited considerably longer yawns than birds of comparable brain and body mass. These findings provide further evidence suggesting that yawning is a thermoregulatory adaptation that has been conserved across amniote evolution.
Keywords: mozek; velikost orgánu; Yawning; savci; ptáci; Birds; zívání; Animals; Mammals; Organ Size; neurony; zvířata; Neurons; Brain